Uso de plaguicidas en el valle del río Carrizal - Pazmiño Pazmiño, Gema Monserrate (2023)
The objective of this research was to characterize the use of pesticides in the Carrizal River valley. It is a descriptive research, in which a survey was applied to 220 producers. The questionnaire consisted of 33 questions of open and closed options, which was validated under the methodology of experts. As a result, 62.3% of the crops are managed by men between 36 and 45 years of age; 50% of the farmers studied only primary school; 7.3% have required financing from banks to plant their crops. Of those surveyed, 17.7% are members of an association. It was determined that 84.4% of the surface area of the properties is between 0 and 5 hectares, 25% of the farmers dedicate their time to corn production, 19% to banana, 18% to cocoa, 10% to citrus, 4% to beans, 3% to rice, and 22% to other crops such as cassava, avocado, coffee, among others, 41% of which are perennial crops. The most commonly used pesticides are herbicides 65% (glyphosate 37%, paraquat 43%, 2,4-dichlorophenoxyacetic acid 13%, and 2,4-D Amina+ Picloram 9%) insecticides 29% and fungicides 3%. 32% of farmers who use herbicides are more likely to suffer from hypertension, 9% suffer from diabetes, and 6% of farmers suffer from allergies after using herbicides.